2012
DOI: 10.1038/nn.3084
|View full text |Cite
|
Sign up to set email alerts
|

The animal and human neuroendocrinology of social cognition, motivation and behavior

Abstract: Extensive animal and recent human research have helped inform neuroendocrinological models of social cognition, motivation and behavior. In this review, we first summarize important findings regarding oxytocin, arginine vasopressin and testosterone in the domains of affiliation, social cognition, aggression and stress/anxiety. We then suggest ways in which human research can continue to profit from animal research, particularly by exploring the interactive nature of neuromodulatory effects at neurochemical, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
189
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(202 citation statements)
references
References 96 publications
11
189
1
1
Order By: Relevance
“…Our results then suggest that women's testosterone levels modulate the motivational salience of facial attractiveness, consistent with the results of studies in which administering testosterone to women increased responses to financial incentives in brain regions implicated in motivation and reward processing (Hermans et al, 2010). Consequently, our data present new, converging evidence that testosterone plays a potentially important role in reward sensitivity (McCall & Singer, 2012). Some prior work suggests that viewing faces in general is rewarding (e.g., Kawabata & Zeki, 2008).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results then suggest that women's testosterone levels modulate the motivational salience of facial attractiveness, consistent with the results of studies in which administering testosterone to women increased responses to financial incentives in brain regions implicated in motivation and reward processing (Hermans et al, 2010). Consequently, our data present new, converging evidence that testosterone plays a potentially important role in reward sensitivity (McCall & Singer, 2012). Some prior work suggests that viewing faces in general is rewarding (e.g., Kawabata & Zeki, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…Some prior work suggests that viewing faces in general is rewarding (e.g., Kawabata & Zeki, 2008). This being the case, that we found the motivational salience of faces in general to be greater when testosterone levels were high also supports McCall and Singer's (2012) proposal.…”
Section: Discussionsupporting
confidence: 87%
“…Steroids can also modify cognitive processes ranging from attention (38) to learning (2, 3) that affect the probability and quality of a particular behavioral response. Our studies of the neural basis of how T regulates song behavior illustrate two important principles.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in both monkeys and humans have suggested that it has not only evolved a more extensive role in social cognition in female primates but also become progressively used by males in this domain (3). Although OXT appears to facilitate both salience and motivational aspects of social cues in both sexes (3,4), there is increasing evidence that it may often produce opposite effects in these domains in men and women (5)(6)(7), raising the intriguing possibility that it has evolved some sex-specific functions at both neural and behavioral levels.…”
mentioning
confidence: 99%
“…Recent studies in both monkeys and humans have suggested that it has not only evolved a more extensive role in social cognition in female primates but also become progressively used by males in this domain (3). Although OXT appears to facilitate both salience and motivational aspects of social cues in both sexes (3,4), there is increasing evidence that it may often produce opposite effects in these domains in men and women (5)(6)(7), raising the intriguing possibility that it has evolved some sex-specific functions at both neural and behavioral levels. In particular, behavioral studies have reported that whereas OXT tends to facilitate positive social judgments (7), social approach (8), kinship recognition (5), and altruism (9) in women, in men it can facilitate negative social judgments (7), social avoidance (10), competitor recognition (5), and selfishness (9).…”
mentioning
confidence: 99%